Դարի և պարսկերեն լեզուների բառային կազմերի համեմատական–համադրական ուսումնասիրության շուրջ - Փարսադանյան, Վրեժ (Ասողիկ հրատ.)
This study is the first attempt in investigating the comparative word-fomiation in modern Dari and Farsi languages. The work embraces semantical, morphological and wordbuiiding aspects of Dari and Farsi and their interrelations conducted by the author. The outcome of the studies, most probably, may have a significant importance both from the viewpoint of carrying out fundamenta! historical and comparative studies and of solving some specific practica! problems referring, mainly, to compiling manuals, textbooks, dictionaries in Dari and Farsi as well as doing translation work.
Keywords: Լեզվաբանություն; Պատմություն